2015
DOI: 10.2319/080414-544.1
|View full text |Cite
|
Sign up to set email alerts
|

Does clinical experience affect the reproducibility of cervical vertebrae maturation method?

Abstract: The reproducibility of the method was not improved by the level of orthodontic experience. The group with the lowest level of orthodontic experience had the best performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Also, findings from Rongo et al indicated that the CVM method reproducibility was not improved by the level of experience in orthodontic practice, as the group with less than 1 year of clinical experience yielded better results. 32 The Greulich and Pyle method 24 for the HW evaluation and the CVM method of Baccetti and coworkers 12 were chosen due to the quicker and more user-friendly approaches. 12,33 The validity and reliability of the CVM method in comparison with HW assessments have been investigated in a series of studies over the years, mainly through correlation and agreement coefficients, such as: ICC, Cohen's κ coefficient, Kendall's W coefficient, Pearson and Spearman correlation tests.…”
Section: Staging Hand-wrist and Cervical Vertebrae: A Reproducibilitymentioning
confidence: 99%
“…Also, findings from Rongo et al indicated that the CVM method reproducibility was not improved by the level of experience in orthodontic practice, as the group with less than 1 year of clinical experience yielded better results. 32 The Greulich and Pyle method 24 for the HW evaluation and the CVM method of Baccetti and coworkers 12 were chosen due to the quicker and more user-friendly approaches. 12,33 The validity and reliability of the CVM method in comparison with HW assessments have been investigated in a series of studies over the years, mainly through correlation and agreement coefficients, such as: ICC, Cohen's κ coefficient, Kendall's W coefficient, Pearson and Spearman correlation tests.…”
Section: Staging Hand-wrist and Cervical Vertebrae: A Reproducibilitymentioning
confidence: 99%
“…A precise diagnosis is essential for choosing the correct therapy and determining the prognosis adequately. Therefore, orthodontic treatment planning requires an accurate prediction of the amount and direction of craniofacial development [2][3][4]. Since Broadbent [5] introduced lateral cephalometric radiography in 1931, studies on craniofacial growth and development have increased in number and many researchers have suggested definitions and norms for the normal occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…analyzing the cervical vertebrae maturation method 17 and undergraduate students showed better volumetric landmark location in 3-dimensional images than orthodontic residents, 18 confirming that the level of experience do not always improve reliability. The intra-observer weighted kappa coefficients of suture-FS were substantial for both observers.…”
Section: Discussionmentioning
confidence: 93%